Integrating Spiritual-Based Character Education: A Case Study of Curriculum Restructuring at Madrasah Aliyah Negeri Bojonegoro - Wahid, Abdul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The inculcation of character traits, including behaviour, knowledge and skills, is a crucial element in ensuring academic success. Nevertheless, the absence of character education integration into formal curricula has resulted in moral concerns. In response to this situation, MAN 1 and MAN 2 Bojonegoro have implemented a restructuring of their curricula, which now includes the incorporation of spiritual-based character education. This multi-case study, employing qualitative methods with a descriptive-analytical approach, revealed that the integration occurs in three stages: The process of integration can be divided into three stages: 1) Planning, which involves defining spiritual values, academic culture, and teaching materials; 2) Implementation, incorporating both extracurricular and co-curricular activities; and 3) Evaluation, which includes testing and persuasive techniques. The internalisation of character education is based on a comparison system that aligns teaching materials with the aforementioned character education elements and an analysis system focusing on the future vision of the madrasah. The findings of this study indicate that all educational institutions should consider reconstructing their curricula to integrate spiritual character education into the core principles, goals, methodologies, and content.